Anti-RANKL Inhibits Thymic Function and Causes DRONJ in Mice. (15th April 2022) - Nakamura, Yusuke; Kikuiri, Takashi; Sugiyama, Takahiro; Maeda, Ayako; Izumiyama, Daisuke; Yahata, Daigo; Yoshimura, Yoshitaka; Shirakawa, Tetsuo; Kitagawa, Yoshimasa
Abstract : Background . Denosumab, a human monoclonal antibody against receptor activator of nuclear factor-kappa B ligand (RANKL), is a novel bone antiresorptive agent used in patients with osteoporosis or metastatic bone cancer. Denosumab-related osteonecrosis of the jaw (DRONJ) has been recently reported in patients using denosumab. However, the mechanisms of DRONJ are not fully understood. Appropriate pathogenic mechanisms of DRONJ have yet to be established. Therefore, we investigated the pathogenesis of DRONJ in mice. Methods . Anti-mouse RANKL monoclonal antibody and melphalan were performed to create a mouse model of DRONJ-like lesions in female C57BL/6J mice. We examined the development of DRONJ-like lesions and immune function. Results . We showed that administration of anti-mouse RANKL monoclonal antibody and melphalan caused DRONJ-like lesions that recapitulated major clinical manifestations of the human disease, including the characteristic features of an open alveolar socket and exposed necrotic bone. In the analysis using a mouse model of DRONJ-like lesion, it was revealed that anti-mouse RANKL monoclonal antibody and melphalan suppress autoimmune regulator (AIRE) expression in the thymus and imbalanced T cell populations. Conclusion . This study suggests evidence of an immunity-based mechanism of DRONJ-like disease. This work may contribute to a better understanding of the pathogenesis of human DRONJ.